OPTIMIZATION OF ENERGY EFFICIENCY PERFORMANCE AND SPACE COMFORT IN COWORKING SPACE BUILDING, CASE STUDY: RELATIONSHIP OF COWORKING SPACE AND CAFE - Agustina Tri Mulyani; Christian Nindyaputra Octarino (Lakar: Jurnal Arsitektur, 2023)
After the COVID-19 pandemic, people began to embrace flexible working and coworking space became one of the comfortable work spaces. The culture of "work from anywhere" has begun to be commonly applied in various business sectors. The  comfort of coworking  space has an impact on the need for high energy consumption. This study aims to evaluate the performance  of coworking space buildings  in terms of energy efficiency and user comfort. The method used is a quantitative method with mathematical calculation analysis and also software simulation. The research focuses on optimizing energy efficiency through the performance of the building envelope, then the parameters used are OTTV to show the level of heat conduction, IKE as the overall level of energy consumption, and spatial comfort in the visual aspect. The results of the existing evaluation show a fairly high energy consumption of 230 kWh / m2 / year. Several design strategies in an effort to improve the energy efficiency performance of buildings include modifying building envelope materials with low thermal conductivity (u-value) characteristics, as well as providing alternative shading designs for buildings to be able to reduce incoming heat more optimally. Simulations show that the recommended design strategy can reduce OTTV value by up to 50% and IKE value to 173 kWh/m2/year. Thus, energy efficiency strategies  with low u-value materials (reflective exterior layers, low-e glass with air gaps  and  green roofs) for building envelopes and passive design through shading device  design interventions are considered effective in supporting the needs of coworking space comfort standards.